2007
DOI: 10.1614/ws-06-084.1
|View full text |Cite
|
Sign up to set email alerts
|

Fluroxypyr Efficacy is Affected by Relative Humidity and Soil Moisture

Abstract: An experiment was conducted in controlled environments to evaluate the effects of relative humidity (RH) and soil moisture (SM) on fluroxypyr efficacy on kochia and Palmer amaranth. Plants were grown in growth chambers with constant RH of 35 or 90 ± 5% and 28/23 C day/night temperature. Within each growth chamber, plants were grown in SM regimes of either −20 or −40 kPa. When plants were 8 to 10 cm tall, fluroxypyr was applied at 26, 52, 78, or 104 g ae ha−1; a nontreated control was included. At 21 days after… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
9
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 18 publications
1
9
0
Order By: Relevance
“…Nevertheless, it is reasonable to anticipate better control results with applications to well-watered, unstressed yellow starthistle plants. Similar reductions in efficacy of auxinic herbicides under drought stress conditions have been demonstrated in many studies, e.g., Basler et al (1961) with 2,4-D on dry beans; Lubbers et al (2007) with fluroxypyr on kochia [Kochia scoparia (L.) Schrad.] and Palmer amaranth (Amaranthus palmeri S.…”
Section: Resultssupporting
confidence: 75%
“…Nevertheless, it is reasonable to anticipate better control results with applications to well-watered, unstressed yellow starthistle plants. Similar reductions in efficacy of auxinic herbicides under drought stress conditions have been demonstrated in many studies, e.g., Basler et al (1961) with 2,4-D on dry beans; Lubbers et al (2007) with fluroxypyr on kochia [Kochia scoparia (L.) Schrad.] and Palmer amaranth (Amaranthus palmeri S.…”
Section: Resultssupporting
confidence: 75%
“…Therefore, A. palmeri grown under field condition will have better chance of survival and higher seed production due to limited periods of water stress compared with continuous water stress conditions in this study. Previous research has shown reduced control of different weed species, including A. tuberculatus , with POST herbicides when grown under high soil water stress conditions, due to reduced herbicide retention, absorption, or translocation (Lubbers et al 2007; Morrison et al 1995; Ruiter and Meinen 1998; Skelton et al 2016; Zhou et al 2007). Therefore, more research needs to be conducted regarding herbicide efficacy on A. palmeri plants under varying water stress levels.…”
Section: Resultsmentioning
confidence: 99%
“…Activity of foliar herbicide sprays can be influenced by the environmental conditions at the time of spraying (Ramsey, 2003;Lubbers et al, 2007;Idziak and Woznica, 2009). Effectiveness of herbicides is also strongly modified by biological properties of the target weeds and spray liquid properties.…”
Section: Resultsmentioning
confidence: 99%